Effects of Nitrogen and Sulfur Deprivation on β-Carotene and Fatty Acid content of Dunaliella salina - Hannaneh Khademi; Mohammad Hossein Morowvat; Younes Ghasemi (Shiraz University of Medical Sciences, 2018)
Dunaliella salina a green unicellular chlorophycean microalga, is famous as a robust carotenoid, fatty acids and also biomass producer. Biomass, lipid and β-carotene levels in D. salina increases during nutrient deprivation conditions. In this study the effects of nitrogen and sulfur starvation, on β-carotene, lipid and biomass production and composition in a naturally isolated D. salina strain was studied. Johnson culture medium was exploited for subculturing and growth of the studied strain. Direct cell counting method and also dry cell weight measurement were used for monitoring the cell growth. β-carotene production was measured using spectrophotometry method. The experiments were performed in 22 days with two different growth stages composed of 8 days of nutrient rich and 14 days of nitrogen and sulfur deprived media. The studied microalgal strain showed a higher biomass production and cell growth rate in comparison with the starvation condition. Moreover, a significant increase of cellular β-carotene and lipid contents was observed under nitrogen and sulfur limitation. The studied microalgal strain contained some important fatty acid with food, feed and biodiesel potentials. The obtained results suggested the applicability of macroelements deprivation strategy to elevate the carotenoids and lipid accumulation in D. salina with the minimum biomass reduction.